Clinical significance of substantially elevated von Willebrand factor antigen levels in patients with advanced chronic liver disease. Issue 10 (October 2022) - Pomej, Katharina; Scheiner, Bernhard; Balcar, Lorenz; Nussbaumer, Rosa Johanna; Weinzierl, Johanna; Paternostro, Rafael; Simbrunner, Benedikt; Bauer, David; Pereyra, David; Starlinger, Patrick; Stättermayer, Albert Friedrich; Pinter, Matthias; et al.
Abstract: Background: Von Willebrand factor antigen (VWF) is a non-invasive marker for clinically significant portal hypertension (HVPG≥10 mmHg) and confers HVPG-independent prognostic information. While quantification of increased VWF-levels is not relevant in the context of von Willebrand disease, highly elevated VWF may be of clinical significance in ACLD. Thus, we have modified our analytical approach to quantify very high VWF-levels (i.e., >420%) and investigated their prognostic value. Methods: Patients undergoing HVPG-measurement at the Vienna Hepatic Hemodynamic Lab with evidence of ACLD and information on VWF were considered. Clinical stages (CS) were defined as follows: Probable compensated ACLD (cACLD): LSM≥10kPa&HVPG<6 mmHg; 0: cACLD&6–9 mmHg; 1: cACLD&HVPG≥10 mmHg; 2: bleeding; 3: non-bleeding decompensation; 4: ≥2 decompensations. Results: 124 (16%) of 793 patients had VWF>420%. The proportion of VWF>420% increased with disease severity (probable cACLD-0: 5(4%) vs. 1: 22(10%) vs. 2–4: 97(23%), p ≤ 0.001) as well as across HVPG (<6mmHg: 1(2%) vs. 6–9: 6(6%) vs. 10–15: 17(9%) vs. ≥16: 100(22%), p ≤ 0.001) and MELD (<10: 17(6%) vs. 10–14: 27(10%) vs. ≥15: 79(32%), p ≤ 0.001) strata. In patients with VWF>420%, median VWF was 533 (IQR:466–611)% and VWF was unrelated to HVPG (Spearman's ρ=0.139, p = 0.123), but showed direct correlations of weak/moderate strength with MELD (ρ=0.336, p < 0.001) and CRP (ρ=0.286, p = 0.001). In the subgroup with VWF>420%, VWF was predictive of decompensation/liver-related mortality (VWF per 10%; hazard ratio (HR): 1.02(95% confidence interval (95%CI): 1.01–1.04), p = 0.008, even after adjusting for other factors (VWF per 10%; adjusted HR: 1.02(95%CI: 1.00–1.05), p = 0.031). Conclusion: The proportion of patients with substantially elevated VWF values steadily increases with disease progression. While VWF is not reflective of HVPG in these patients, it is correlated with hepatic dysfunction and systemic inflammation. Importantly, quantification of high values provides prognostic information.